Pemanfaatan buah sukun sebagai kripik untuk meningkatkan perekonomian masyarakat Desa Buntu Batuan - Shadiq, Aqil; Putri, Nurhalisa; Amin, Muhammad Akbar; Desna; Anugrah; Ramadhani, Alifiah Rifti; Farhan, Ilham; Ismawati; Putri, Namira; Astuti, Intan; Fadillah, Nurul Adin (P3HKI - Universitas Muhammadiyah Parepare, 2021)
Dusun Duri-Duri in Buntu Batuan Village, Enrekang Regency, faces economic challenges due to the instability of agricultural market prices. One proposed solution is the development of Micro, Small, and Medium Enterprises (MSMEs) based on local agricultural products. This program aims to process breadfruit into a high-value product called Sukuri Chips. The implementation method includes observation, production training, marketing strategies, and sustainability evaluation. The results of this program indicate an increase in community skills in breadfruit processing, heightened awareness of product innovation, and opportunities for income growth through product marketing. The sustainability of this program requires further assistance and support from the government and relevant stakeholders to strengthen agriculture-based MSMEs in the region.